The Effect of Work-Life Balance, Green Compensation, And Reward on Employee Sustainable Performance Through Employee Engagement as a Mediating Variable - Heri Sunandar; M. Ali Iqbal (International Journal Labs, 2026)
This study aims to examine and analyze the effects of work-life balance and green compensation and reward on employee sustainable performance through employee engagement as a mediating variable. The population consists of all permanent employees (PKWTT) of PT. OEKA, an oil and gas company operating in the Karang Agung Block, South Sumatra, totaling 188 employees. A sample of 128 respondents was determined using the Slovin formula, employing probability sampling with a simple random sampling technique. Data were collected through a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.1. The results show that work-life balance has no significant direct effect on employee sustainable performance, whereas green compensation and reward and employee engagement each have a positive and significant effect on employee sustainable performance. Both work-life balance and green compensation and reward have a positive and significant effect on employee engagement. Furthermore, employee engagement fully mediates the effect of work-life balance on employee sustainable performance, and partially mediates the effect of green compensation and reward on employee sustainable performance. These findings highlight the strategic role of employee engagement in achieving sustainable employee performance through sustainability-oriented human resource practices in the oil and gas sector.